Germany in Central America : competitive imperialism, 1821-1929 - Schoonover, Thomas David, 1936- (University of Alabama Press, 1998)
Of the four countries most active in independent Central America - Britain, the United States, France, and Germany - historians know the least about the full extent of the involvement of the Germans. Germany, however, played a crucial role in Central American history. Germany in Central America reveals the stories of the institutions that supported and organized German migration, the immigrants' continuing ties with the homeland, and the preservation of their culture on foreign soil. This unique book traces the political and economic changes in Germany (and to some extent also in Central America) to serve as background for narrating or analyzing the relationship between Germany and Central American countries. Schoonover utilizes extensive private and public manuscript material from Central America, Europe, and the United States, including private collections and German federal and state government archives, to reveal this relationship within the framework of the rivalry of European powers and the United States.